TropD-detector a CRISPR/LbCas12a-based system for rapid screening of Trypanosoma cruzi in Chagas vectors and reservoirs - Luis A. Ortiz-Rodríguez; Rafael Cabanzo; Jeiczon Jaimes-Dueñez; Stelia C. Mendez-Sanchez; Jonny E. Duque (Scientific Reports)
Abstract Chagas disease, also known as American Trypanosomiasis, is a zoonosis with global distribution caused by the parasite Trypanosoma cruzi, primarily transmitted through the feces of infected triatomines. The emergence of new cases highlights the importance of early pathogen detection in vectors and reservoirs to generate effective control strategies and establish preventive policies. The objective of this study was to design and validate a detection system of T. cruzi based on specific DNA cleavage, activation of Cas12a and trans-cleavage, targeting the genes Cytochrome B (Cytb), 18 S ribosomal subunit (SR18 s), and histone (H2 A). This system was validated for their uses in both vectors and reservoirs of the parasite. The initial step involved performing a bioinformatic analysis of the target genes, followed by the design of RNA guides specific to each cleavage site, along with primers for amplifying the target region through PCR and RPA. Subsequently, we sequenced the amplified DNA target and validated the detection system using T. cruzi DNA extracted from naturally infected Rhodnius pallescens in the metropolitan area of Bucaramanga, Colombia. After standardizing the method, we tested the CRISPR/Cas system with Silvio X10 laboratory strain of T. cruzi and scaled up to blood samples of naturally infected Didelphis marsupialis. As a result, we observed DNA cleavage using the CRISPR/Cas system with the Cytb guide, achieving a detection sensitivity of 118 parasite equivalents/mL in PCR and 116 parasite equivalents/mL with RPA amplification. Sequencing of the Cytb gene showed no mutations in the cleavage site. However, point mutations and indels were found in SR18S and H2 A, avoiding the formation of the CRISPR/LbCas12 complex. Furthermore, we introduce the design of a fluorescent detection prototype with CRISPR/LbCas12a called “Tropical Diseases Detector” (TropD-Detector). This device operates with an excitation wavelength of 480 nm emitted by an LED and a high-pass light filter with a cutoff wavelength of 500 nm. We detected positive samples using any photographic camera system. The TropD-Detector provides a visual, viable, and sensitive method for detecting T. cruzi in both vectors and reservoirs from endemic areas.